Development of overweight permit fee using mechanistic-empirical pavement design and life-cycle cost analysis - Wang, Hao; Zhao, Jingnan (Transport, 2016)
The study aims to determine rational overweight permit fee using Mechanistic-Empirical (M-E) pavement design and Life-Cycle Cost Analysis (LCCA). The state-of-art pavement design software, Pavement-ME, was utilized to develop Load Equivalency Factors (LEFs) and estimate pavement service life under various traffic loading conditions. LCCA was conducted to calculate Marginal Pavement Damage Cost (MPDC) in terms of Equivalent Uniform Annual Cost (EUAC) considering variations in maintenance strategies, analysis periods, and discount rates. A methodology framework was established to calculate distance based, weight based, weight and distance based, and flat permit fee for overweight trucks. With the local data obtained in New Jersey (United States), example permit fees were determined for the major and local road network with the thick and thin asphalt pavement structure, respectively. It was found that the truck-induced damage cost varied significantly between thin and thick asphalt pavements considering different failure mechanisms in fatigue cracking and rutting. In general, overweight permit fee may not be fair to overweight trucks at different vehicle classifications if only the total overweight tonnage is regulated in the permit fee structure.